The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1016/j.ceramint.2020.01.134
|View full text |Cite
|
Sign up to set email alerts
|

Fast drying of high-alumina MgO-bonded refractory castables

Abstract: Refractory producers face many challenges in terms of producing MgO-containing castables due to the high likelihood of magnesia to hydrate in contact with water, resulting in Mg(OH)2 generation. The expansive feature of this transformation affects the performance of such refractories, as (i) if this hydrated phase is not accommodated in the formed microstructure, ceramic linings with cracks and low green mechanical strength will be obtained; and (ii) if crack-free pieces are prepared, they should present low p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 34 publications
0
23
0
Order By: Relevance
“…Reports in the literature suggest that the soluble salts could be replaced by reactive oxides as cation sources [17][18][19]. In these cases, hydration/hydrolysis reactions would provide the desired ions, excludi process [17-Authors' hydrotalcite and magnes alumina or c simply by c suspension, w steps [20] A n-A n-A n- According to the XRD results (Fig. 2), AL addition to the MgO-suspensions inhibited brucite formation.…”
Section: Materials and Techniquesmentioning
confidence: 99%
See 1 more Smart Citation
“…Reports in the literature suggest that the soluble salts could be replaced by reactive oxides as cation sources [17][18][19]. In these cases, hydration/hydrolysis reactions would provide the desired ions, excludi process [17-Authors' hydrotalcite and magnes alumina or c simply by c suspension, w steps [20] A n-A n-A n- According to the XRD results (Fig. 2), AL addition to the MgO-suspensions inhibited brucite formation.…”
Section: Materials and Techniquesmentioning
confidence: 99%
“…Authors' previous work has reported on the formation of hydrotalcite in some systems comprised by a blend of alumina and magnesia reactive sources (respectively, hydratable alumina or calcium aluminate cement and caustic magnesia), simply by combining these raw materials in an aqueous suspension, with no need of additional reactants or purification steps [20]. This paper presents and discusses this process route in order to produce hydrotalcite.…”
Section: -Aluminum Lactate Effects On Mgo Hydration Behaviormentioning
confidence: 99%
“…After the cooling step, the elastic modulus of 3.2CC and 3.2CC_0.5L (120 and 115 GPa, respectively) were higher than the reference composition 6CAC (~110 GPa). However, there are two differences between refractories 3.2CC and 3.2CC_0.5L that are relevant to point out: i) the presence of the aluminum lactate gel after the drying step explains the higher initial elastic modulus of the latter (70 versus 40 GPa); and ii) its decomposition at ~375 °C [14,25] increased the porosity content in the microstructure, causing a stiffness drop of the samples in the 300-400 °C range. Furthermore, Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Although it was observed a drop in the HMOR values measured between 1200-1450 °C, the results obtained for 3.2CC and 3.2CC_0.5L were still similar to the ones of the reference 6CAC. Moreover, the aluminum lactate gel provided a better thermomechanical performance at 300 °C for 3.2CC_0.5L when compared to 3.2CC (5 versus 3 MPa), whereas its decomposition at ~375 °C [14,25] gave rise to pores in the resulting microstructure (Fig. 5b), which affected its hot modulus of rupture at higher temperatures (600-1450 °C).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation